Effect of controlling white-backed planthopper on the occurrence of southern rice black-streaked dwarf disease - Wang Daoze; Hong Wenying; Wu Yanjun; Hu xuanxiang; Wang Yanxin (浙江大学学报. 农业与生命科学版)
In recent years, southern rice black-streaked dwarf virus (SRBSDV) has spread rapidly in Southern China and caused a serious viral dwarf disease. The white-backed planthopper (WBPH) Sogatella furcifera is a main vector for SRBSDD transmission. Use of disease resistant cultivars and insect vector control are the most economical and environmentally friendly strategy for arboviral disease control. This research focused on the resistance to SRBSDD among different rice varieties. The relationship between density of insect vectors and occurrence degree of SRBSDD was examined, and the effectiveness of disease management with controlling WBPH was measured, to build a predictive model for the occurrence of disease and damage degree of SRBSDD.In this study, we investigated the population dynamics of WBPH on 17 rice varieties in Hangzhou, China and created a predictive model for SRBSDD. The results showed that the population densities of WBPH and the disease indexes of SRBSDD on different rice varieties were significantly different, which were highest on the four rice varieties, including Yueyou 9113, Tianyouhuazhan, Y-Liangyou 2 and New-Liangyou 6. Statistical analysis demonstrated that the disease index of SRBSDD was significantly positively correlated with the population density of WBPH. For example, the disease index of SRBSDD at heading stage (Y1) was significantly positively correlated with the population density of WBPH in early August (X2) or early September (X4). The predictive model for SRBSDD was Y1=-7.962+0.110X2+2.505X4(r=0.808, P<0.000 6). The results confirmed the critical role of WBPH in primary infection during seedling stage to early growth stage and in secondary infection of SRBSDV, which affected the occurrence degree of SRBSDD significantly.Meanwhile, we compared the population density of WBPH and control effectiveness of SRBSDD after different pesticide treatments. The seed treatment of imidacloprid FS and the foliar application of Virtako WG 40% (chlorantraniliprole 20% + thiamethoxam 20%) decreased spread of SRBSDV by 61.7% and 73.2% respectively. The control effectiveness and disease indexes of SRBSDD showed a significant positive relationship with the population density and control effectiveness of WBPH.In conclusion, it is possible to predict the occurrence degree of SRBSDD, based on the population density of WBPH at early growth phase of rice. Using seed treatments and foliar applications of pesticides at seedling stage or early growth phase of rice is an effective way to control the disease by decreasing the major primary infection source of SRBSDV.